Legal geography
1 online resource (xvii, 310 pages)
Keywords: "This book is the first legal geography book to explicitly engage in method. It complements this by also bringing together different perspectives on the emerging school of legal geography. It explores human-environment interactions and showcases distinct environmental legal geography scholarship. Legal Geography: Perspectives and Methods is an innovative book concerned with a new relational and material way of examining our legal-spatial world. With chapters examining natural resource management, Indigenous knowledge, and political ecology scholarship, the text introduces legal geography's modes of analysis and critique. The book explores topics such as indigenous environmental rights, the impacts of extractive industries, mediation of climate change, food, animal and plant patents, fossil fuels, mining, and coastal environments based on empirical, jurisdictional and methodological insights from Australia, New Zealand, and the Asia Pacific to demonstrate how space and place are invoked in legal processes and contestations, and the methods that may be invoked to explore these processes and contestations. This book examines the role of legal geographies in twenty first century beyond the simple 'law in action', and it will thus appeal to students of socio-legal studies, human geography, environmental studies, environmental policy, as well as politics and international relations"--